Clinical features and biological markers of lung cancer-associated stroke. (December 2016) - Xie, Xingrui; Chen, Li; Zeng, Jinsheng; Qin, Chao; Cheng, Daobin; Wei, Xinxian; Liang, Zhijian
Objective: To identify the unique clinical features and biological markers of lung cancer-associated stroke. Methods: We recruited 102 patients with lung cancer plus stroke, 102 with lung cancer, and 102 with stroke. Detailed information was analysed and compared among groups. Results: The groups were age-matched. Patients with lung cancer plus stroke showed multiple lesions involving multiple cerebral artery territories on magnetic resonance imaging, compared with stroke-alone patients. These patients also had a poorer modified Rankin Scale score at 30 days, and high mortality (18.6%). Patients with lung cancer plus stroke had a higher incidence of metastasis, and higher blood levels of D-dimer, CA125 and CA199 compared with patients with lung cancer alone. Multivariate logistic regression analysis showed that levels of D-dimer, CA125 and CA199 were independently related to lung cancer-associated stroke. Conclusion: Elevated plasma D-dimer, CA125 and CA199 may be independent risk factors for and biomarkers of lung cancer-associated stroke.